A Mobile Detector for Muon Measurements Based on Two Different Techniques - B. Mitrica; D. Stanca; M. Petcu; I. M. Brancus; R. Margineanu; A. Apostu; C. Gomoiu; A. Saftoiu; G. Toma; H. Rebel; A. Haungs; O. Sima; et al. (Advances in High Energy Physics)
Precise measurements of the muon flux are important for different practical applications, both in environmental studies and for the estimation of the water equivalent depths of underground sites. A mobile detector for cosmic muon flux measurements has been set up at IFIN-HH, Romania. The device is used to measure the muon flux on different locations at the surface and underground. Its first configuration, not used in the present, has been composed of two 1 m2 scintillator plates, each viewed by wave length shifters and read out by two Photomultiplier Tubes (PMTs). A more recent configuration, consists of two 1 m2 detection layers, each one including four 1 · 0,25 m2 large scintillator plates. The light output in each plate is collected by twelve optical fibers and then read out by one PMT. Comparative results were obtained with both configurations.